2018
DOI: 10.1007/s11223-018-9994-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Depth of the Deformed Layer in the Roller Burnishing Process

Abstract: à Òåõíîëîãî-ãóìàí³òàðíèé óí³âåðñèòåò ³ì. Êàçèìèðà Ïóëàâñüêîãî â Ðàäîì³, ²íñòèòóò ìàøèíîáóäóâàííÿ, Ðàäîì, Ïîëüùà á Òåõíîëîã³÷íèé óí³âåðñèòåò AEåøóâà, Ôàêóëüòåò ìàøèíîáóäóâàííÿ òà àåðîíàâòèêè, AEåøóâ, Ïîëüùà Íàâåäåíî ìåòîäèêè âèçíà÷åííÿ ãëèáèíè ïëàñòè÷íî äåôîðìîâàíîãî âåðõíüîãî øàðó ìàòåð³àëó ïðè îáêî÷óâàíí³ ðîëèêîì. Àíàë³òè÷íèé ìåòîä ðîçðîáëåíî íà îñíîâ³ òåî𳿠Ãåðöà-Áåëÿºâà. Ãëèáèíó òàêîãî øàðó îòðèìàíî ÿê ôóíêö³þ çóñèëëÿ îáêî÷óâàííÿ, ì³öíîñò³ ìàòåð³àëó ³ ãåîìåò𳿠ðîëèêà. Àíàë³òè÷íèé ðîçâ'ÿçîê ïåðåâ³ðåíî îðèã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…The original technology includes the following stages [37]: powder mixture preparation; separate pressing of the parts to obtain workpieces of a given shape, sizes, and density (Fig. 4); applying of the fine powder suspension of the same alloy composition on the joined surfaces; and sintering, which combines with diffusion welding and infiltration by copper.…”
Section: Materials Original Equipment Experimental Techniques and mentioning
confidence: 99%
“…The original technology includes the following stages [37]: powder mixture preparation; separate pressing of the parts to obtain workpieces of a given shape, sizes, and density (Fig. 4); applying of the fine powder suspension of the same alloy composition on the joined surfaces; and sintering, which combines with diffusion welding and infiltration by copper.…”
Section: Materials Original Equipment Experimental Techniques and mentioning
confidence: 99%
“…Kowalik et al [ 15 ] proposed a theoretical method of determining the depth of plastic deformation in the RB, based on the Hertz theory. The solution to the problem proposed by Jezierski and Mazur [ 16 ] was based on the simplifying assumption that there are zones of plastic deformation and elastic deformation in the surface layer.…”
Section: Introductionmentioning
confidence: 99%
“…Kowalik et al [22] and Kowalik and Trzepiecinski [23] showed that the depth of the plastically deformed layer in the burnishing process is influenced by the state of stress during roller burnishing process. The asymmetric state of stress caused by the roll braking during burnishing [23] causes a greater depth of plasticised zone in the surface layer of shaft.…”
Section: Introductionmentioning
confidence: 99%